Enchantra - Smith, Kaylie (New York : Forever, 2025)
"When Genevieve Grimm's mother dies, she's left with questions no one can answer--until she receives an invitation to Enchantra, a cursed palace in Italy, frozen in time and shrouded in strange fruit. So when the hostile and sinfully handsome Rowin Silver refuses to let her inside, Genevieve finds her own way in ... only to realize her mistake. For Enchantra is a twisted labyrinth, carved from gleaming silver and thorned hedges, where Rowin and his six siblings are forever trapped in a deadly game, at the mercy of a wicked Devil and his ghastly spectators. Only one occupant of the house can survive. Genevieve now must win or die. Rowin warns her he's the deadliest of the Silvers. That he always wins. That her only chance is to compete as his wife ... so they must convince their audience that they're desperately in love. And while Genevieve's willing to do whatever it takes to survive, she knows she can't trust Rowin, that the desire burning between them is a lie. After all, it was Rowin who taught her Enchantra's first rule ... Never, ever trust your heart"--
First published in the UK by Second Sky in 2025.
Keywords: Blessing and cursing -- Fiction; Labyrinths -- Fiction; Games -- Fiction; Man-woman relationships -- Fiction; Demonology -- Fiction; Italy -- Fiction; Romance fiction; Fantasy fiction